Degradasi Moral: Penguatan Pendidikan Karakter Melalui Lensa Filsafat Pendidikan Islam - Hayati, Inna Kamilah; Novianti, Novianti; Latifah, Nurul; Tausiah, Azizah; Parhan, Muhamad (Studi Multidisipliner: Jurnal Kajian Keislaman, 2025)
This article examines the strengthening of character education based on the philosophy of Islamic education, which is based on the values of monotheism, morals, and social responsibility. The research approach applied is qualitative, using the literature review method by collecting and analyzing various relevant literature sources. The results of the study show that the integration of the principles of Islamic educational philosophy into the educational curriculum can have a positive impact on the formation of the character of the younger generation, increase moral awareness, and reduce negative behavior. Thus, this article recommends the application of Islamic educational values in the education system to address the problem of moral degradation and form a responsible generation.